2017
DOI: 10.17826/cutf.325571
|View full text |Cite
|
Sign up to set email alerts
|

Hekimlerin organ bağışı konusunda bilgi tutum ve davranışları

Abstract: This study aimed to determine knowledge, attitudes and behaviors of physicians regarding organ donation. Material and Methods: This study was conducted in Kahramanmaras, a city in Mediterranean region of Turkey. The study was conducted between March 1 st and June 9th 2015 by including physicians working in Public Health Centers,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Breast milk bank is defined as "a safe institution for the collection, processing and distribution of donated breast milk" [1] and is based on the concept of "wet-nursing" [10][11][12][13][14][15][16][17][18][19]. Through the pasteurization of breast milk at breast milk banks, harmful pathogens inside the milk are removed while also many of the biologically-active contents are preserved.…”
Section: Definition and History Of The Wet Nursing And Breast Milk Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Breast milk bank is defined as "a safe institution for the collection, processing and distribution of donated breast milk" [1] and is based on the concept of "wet-nursing" [10][11][12][13][14][15][16][17][18][19]. Through the pasteurization of breast milk at breast milk banks, harmful pathogens inside the milk are removed while also many of the biologically-active contents are preserved.…”
Section: Definition and History Of The Wet Nursing And Breast Milk Bamentioning
confidence: 99%
“…Apart from that, the opinions of the society that mothers live in and whether they are given information regarding this situation also affect the outlook on breast milk banks [26,27]. In the studies conducted in Turkey on the opinions of breast milk banks, it is reported that 37.5%-90.6% of mothers do not know about breast milk banks [28][29][30], 28.9%-77.1% do not consider it appropriate from a religious perspective [19,[28][29][30], 75.4%-76.8% do not lean towards milk donation due to the possibility of milk siblings marrying [19,28] and 19.1%-64.0% can donate their breast milk [28,30]. It is worth noting that 85.7% of mothers who have knowledge regarding breast milk banks have acquired this information from sources other than health personnel [29].…”
Section: Studies On Wet Nursing and Breast Milk Banksmentioning
confidence: 99%